USING SITUATIONAL TASKS TO INCREASE THE EFFECTIVENESS OF TEACHING MEDICAL CHEMISTRY - Kh.S. Tadjieva (Web of Journals Publishing, 2024)
Methods of control of knowledge assimilation as testing, solution of situational tasks, problem-based learning tasks are effective innovative methods that used in modern educational process. The use of situational tasks in the control of assimilation of knowledge by students gives an increase in the quality of learning by involving students in independent work, the consequence of which is a high level of knowledge through the development of logical thinking, the ability to work in small groups. In this paper we offer variants of situational tasks, which were applied in the studied groups and the results showed improvement of memorization of chemical compounds formulas, as well as achievement of significant progress in mastering practical skills in the course of experiments.